Mass‐Produced Electrochemically Exfoliated Graphene for Ultrahigh Thermally Conductive Paper Using a Multimetal Electrode System. Issue 9 (26th March 2019) - Kwon, Yeon Ju; Kwon, Youngkook; Park, Ho Seok; Lee, Jea Uk
Abstract: Herein, the development of a cost‐effective system is reported for the mass production of electrochemically exfoliated graphene (EEG) using multiple graphite–stainless‐steel electrodes (multicells) in a series configuration and its application to heat transfer. Exfoliation using series‐configured multicells leads to the production of high‐quality graphene (a few layers of graphene sheets with a low oxygen content and a high C/O ratio of 16.2) at a rate of 30 g per half hour (one‐batch). Furthermore, EEG paper is fabricated by the vacuum filtration of the EEG dispersion, and further thermal annealing and mechanical‐compression processes are used to investigate the effects of heat and pressure on the thermal conductivities of the EEG paper. EEG paper with wide (100–1000 W m −1 K −1 ) and narrow (100–200 W m −1 K −1 ) ranges of thermal conductivity is obtained when thermally annealed and mechanically compressed, respectively, highlighting the high quality of the massively produced and solution processable graphene. This approach provides a cost‐effective process for the mass production of graphene, as well offering a feasible route to highly thermally conductive graphene paper for heat‐management applications, such as heat‐dissipating media in light‐emitting‐diode displays, and electronic and photonic devices. Abstract : Electrochemically exfoliated graphene is mass produced using multiple graphite–stainless‐steel electrodes in series. High‐quality graphene (a few layers of graphene sheets with low oxygen content and a high C/O ratio of 16.2) is produced at a rate of 30 g per half‐hour and annealed or compressed into graphene paper for use in heat‐management applications.